2017
DOI: 10.1038/s41598-017-07889-z
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of the lysosome-dependent autophagic pathway contributes to complement membrane attack complex-induced podocyte injury in idiopathic membranous nephropathy

Abstract: Dysregulation of autophagy-mediated podocyte homeostasis is proposed to play a role in idiopathic membranous nephropathy (IMN). In the present study, autophagic activity and lysosomal alterations were investigated in podocytes of IMN patients and in cultured podocytes exposed to sublytic terminal complement complex, C5b-9. C5b-9 upregulated the number of LC3 positive puncta and the expression of p62 in patient podocytes and in C5b-9 injuried podocyte model. The lysosomal turnover of LC3-II was not influenced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…In this scenario, autoimmune attack could primarily produce autophagy dysfunction, as suggested in our IMNM samples by C5b‐9 deposits in degenerating myofibers, in which there is also a diffuse accumulation of LC3b. Complement membrane attack complex has been demonstrated to inhibit autophagy and lysosomal degradation, increasing the damage to cultured podocytes in an idiopathic membranous nephropathy model and in human disease . Impaired autophagy may also entail the accumulation of damaged mitochondria, as seen in all 3 anti‐HMGCR + IMNM patients, being an additional death trigger.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, autoimmune attack could primarily produce autophagy dysfunction, as suggested in our IMNM samples by C5b‐9 deposits in degenerating myofibers, in which there is also a diffuse accumulation of LC3b. Complement membrane attack complex has been demonstrated to inhibit autophagy and lysosomal degradation, increasing the damage to cultured podocytes in an idiopathic membranous nephropathy model and in human disease . Impaired autophagy may also entail the accumulation of damaged mitochondria, as seen in all 3 anti‐HMGCR + IMNM patients, being an additional death trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers used zymosan to assemble c5b-9 complement complexes, which were developed to interfere with mouse serum to obtain ZaS. Subsequently, ZaS was applied to stimulate podocytes to develop the Mn model in vitro (69)(70)(71) (Fig. 3).…”
Section: Zymosan-activated Serum (Zas)-induced Podocyte Modelmentioning
confidence: 99%
“…Intracellular destruction of endocytic, phagocytic, and autophagic materials is dependent on lysosomes which serve as the major degradative compartments with their digestive function [15][16][17]. Beyond intracellular digestion, lysosomes may mediate cellular signaling in different cells [18][19][20] such as their role in receptor recycling through an endocytic pathway [21] and as a Ca 2+ store importantly participating in the physiological regulation of cell functions or activities in many tissues or cells [19,[22][23][24][25], including podocytes [26][27][28]. In podocytes, normally functioning lysosomes are particularly important for the protection of this terminally differentiated cell type from the challenges of various danger factors [27,[29][30][31].…”
Section: Cellular Functions Regulated By Lysosomesmentioning
confidence: 99%
“…Beyond intracellular digestion, lysosomes may mediate cellular signaling in different cells [18][19][20] such as their role in receptor recycling through an endocytic pathway [21] and as a Ca 2+ store importantly participating in the physiological regulation of cell functions or activities in many tissues or cells [19,[22][23][24][25], including podocytes [26][27][28]. In podocytes, normally functioning lysosomes are particularly important for the protection of this terminally differentiated cell type from the challenges of various danger factors [27,[29][30][31]. Recent clinical and experimental studies have indicated that the deficiency or loss of lysosome function in podocytes results in proteinuria, glomerular sclerosis, and dramatically increased susceptibility to different pathological stimuli [32][33][34][35].…”
Section: Cellular Functions Regulated By Lysosomesmentioning
confidence: 99%
See 1 more Smart Citation